2016
DOI: 10.1111/mve.12157
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cryptic host specificity in duck lice based on molecular data

Abstract: Documenting patterns of host specificity in parasites relies on the adequate definition of parasite species. In many cases, parasites have simplified morphology, making species delimitation based on traditional morphological characters difficult. Molecular data can help in assessing whether widespread parasites harbour cryptic species and, alternatively, in guiding further taxonomic revision in cases in which there is morphological variation. The duck louse genus Anaticola (Phthiraptera: Philopteridae), based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…As many louse specimens in our samples represent undescribed species (Table S1), the 105 new host associations comprise a minimum estimate based on the assumption that all lice belonging to the same genus and parasitizing the same host species represent the same species. It is possible that multiple congeneric species of lice may exist on a single host species (Price et al ., ), especially given that previous studies have shown that different host populations can show high levels of genetic differentiation in their respective lice, resulting in the discovery of cryptic lineages (Voelker et al ., ; Escalante et al ., ). For instance, our Brueelia specimens from Plocepasser mahali mahali represent a different species than material from the same host species (subspecies P. mahali melanorhynchus ) we have seen from Ethiopia (D. Gustafsson, personal observation).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As many louse specimens in our samples represent undescribed species (Table S1), the 105 new host associations comprise a minimum estimate based on the assumption that all lice belonging to the same genus and parasitizing the same host species represent the same species. It is possible that multiple congeneric species of lice may exist on a single host species (Price et al ., ), especially given that previous studies have shown that different host populations can show high levels of genetic differentiation in their respective lice, resulting in the discovery of cryptic lineages (Voelker et al ., ; Escalante et al ., ). For instance, our Brueelia specimens from Plocepasser mahali mahali represent a different species than material from the same host species (subspecies P. mahali melanorhynchus ) we have seen from Ethiopia (D. Gustafsson, personal observation).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, studies using molecular phylogenetics to explore louse diversity in this region are lacking (Sychra et al ., ). Molecular studies exploring parasite diversity are necessary because lice have been shown to exhibit cryptic speciation, and it is often impossible to tell closely related species apart solely based on morphological traits (Escalante et al ., ); African lice are no exception. The importance of molecular studies to identify African louse lineages has been highlighted in recent studies based on lice from the Democratic Republic of the Congo (Light et al ., ) and Benin (Takano et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In birds, feather lice predominantly show vertical transmission from parents to offspring, during brooding and feeding of chicks ( Clayton et al, 2016 ). However, the chewing lice parasitising ducks, geese and swans (Aves: Anseriformes) around the world are among the least specific of all avian lice ( Escalante et al, 2016 ). Whether these parasites are generalists because of the recent radiation of their hosts, because of their hosts’ behaviour and ecology or because of the biology of the lice (i.e., increased dispersal capabilities) is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a recent study of duck lice by Escalante et al. () clades of lice with virtually no COI genetic divergence were found on host taxa across a wide geographic distribution.…”
Section: Discussionmentioning
confidence: 79%
“…Escalante et al. () also found clades of closely related (and morphologically similar) lice occurring on distantly related duck hosts. We also sampled other Colpocephalum complex subgenera from geographically widespread localities (e.g., lice from Buteo jamaicensis ), and these were morphologically and genetically identical.…”
Section: Discussionmentioning
confidence: 93%